Carbon molecular sieve membranes and their use in separation methods
The carbon molecular sieve membrane is pretreated by water vapor to achieve water saturation state, which solves the problem of insufficient purity and efficiency of the existing carbon molecular sieve membrane in gas separation and membrane reactors, and achieves efficient hydrogen separation and solvent dehydration, reducing energy and maintenance cost.
Patent Information
- Application Number
- CN202080092835.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-11
- Filing Date
- 2020-12-10
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-12-10
AI Technical Summary
The existing carbon molecular sieve membranes are insufficient in gas separation and membrane reactors, especially in hydrogen separation and solvent dehydration, and traditional methods have problems of high energy requirements and high maintenance costs.
By pretreating a specific carbon molecular sieve membrane with water vapor to achieve a water saturation state, increasing gas permeability and selectivity, and reducing the permeation of non-adsorbable gases, the pore size distribution and humidification treatment method of the hydrophilic carbon molecular sieve membrane were prepared Water-saturated composite aluminum-carbon molecular sieve membrane with high permeability and selectivity.
The purity of gas separation and the efficiency of the membrane reactor are significantly improved, energy demand and maintenance costs are reduced, and hydrogen and anhydrous solvents are efficiently separated at low temperatures without being affected by external mass transfer restrictions.
Smart Images

Figure HDA0003741130470000011 
Figure HDA0003741130470000021 
Figure HDA0003741130470000031
Abstract
Description
[0001] Cross-reference to prior applications
[0002] This application claims the benefit of European patent application 19383095.7 filed on December 11, 2019. Technical Field
[0003] The present invention relates to the field of gas separation methods, and more specifically to a specific composite carbon molecular sieve membrane pretreated with water vapor and its use in gas separation methods, solvent dehydration and as a membrane reactor. Background Art
[0004] Compared to other technologies, membrane separation methods have relatively low energy requirements and low maintenance costs. Two parameters characterize the separation performance of membranes: permeability and selectivity.
[0005] Carbon molecular sieve membranes (CMSMs) are considered the latest generation of membrane technology due to their unique microporous structure. The main advantage of CMSMs is that their pore size distribution (PSD) can be adjusted to suit the desired separation. The distribution consists of pores of 0.5-2 nm (called micropores or galleries) connected by smaller pores of less than 0.7 nm in size (called ultramicropores). The large micropores provide higher permeation and adsorption sites for strongly adsorbable molecules while reducing the passage of less adsorbable molecules (adsorption-diffusion mechanism); the ultramicropores are responsible for separation via a molecular sieving mechanism, where only molecules with a size smaller than the pores will permeate. The combination of these two transport mechanisms provides the high permeability and selectivity characteristics of these materials.
[0006] MALlosa et al. (“Composite-alumina-carbon molecular sieve membranes prepared from novolac resin and boehmite. Part I: Preparation, characterization and gas permeation studies”, Int. J. Hydrogen Energy. 2015, Vol. 40, pp. 5653–5663) first reported the preparation of 3 μm thick defect-free supported composite alumina-CMSM (Al-CMSM) on an alumina tube (200 nm pore size) using novolac-type phenolic resin and boehmite as precursors through a single-impregnation-drying-carbonization cycle. The pore size and pore size distribution as well as the hydrophilicity of the pores are adjusted by changing the carbonization temperature of the membrane (MALlosa et al. "Composite-alumina-carbon molecular sieve membranes prepared from novolac resin and boehmite. Part II: Effect of the carbonization temperature on the gas permeation properties", Int. J. Hydrogen Energy. 2015, Vol. 40, pp. 3485–3496). Therefore, they reported the effect of carbonization temperature on the pore size distribution and permeation properties of Al-CMSM carbonized at 450°C to 1000°C. The selectivity and permeation properties of the membrane can also be controlled by adjusting the permeation temperature to change the amount of water adsorbed in the pores.
[0007] Separation of hydrogen, which is present in low concentrations in a mixture with methane, is of great importance for the foreseeable hydrogen economy. Hydrogen can be stored and distributed using the existing natural gas network. For safety reasons, the hydrogen content in the distributed gas mixture should be low (approximately 10%). The hydrogen should then be separated at the end user site.
[0008] On the other hand, researchers are constantly working on developing better methods, catalysts and adsorbents to increase the efficiency of fuel and petrochemical production, which is highly dependent on separation methods and their improvement. A good option to solve this problem is the development of membrane reactors. A membrane reactor (MR) is a device that simultaneously performs reactions (steam reforming, dry reforming, autothermal reforming, methanol synthesis, etc.) and membrane-based separations in the same physical device. The continuous extraction of one of the products can change the equilibrium, which improves the yield and selectivity compared to traditional systems.
[0009] In addition, high concentration and anhydrous solvents are very important in the chemical industry, so efficient dehydration methods are being developed. In this case, hydrophilic carbon molecular sieve membranes are very good candidates.
[0010] Therefore, there remains a need for better methods of using CMSMs that allow both higher purity in gas separation processes and better efficiency in membrane reactors and solvent dehydration. Summary of the invention
[0011] The inventors have found that by pre-treating a particular CMSM with water vapor before carrying out a gas separation process in order to obtain a water-saturated membrane, the selectivity of the membrane is significantly increased, and it is performed in a reproducible manner. In particular, in the water-saturated membrane, the water filling of the pores contributes to increasing the permeation of adsorbable gases (adsorption-diffusion mechanism), while increasing the selectivity and reducing the permeation of non-adsorbable gases.
[0012] Therefore, one aspect of the present invention relates to a water-saturated carbon molecular sieve membrane obtainable by:
[0013] i) providing a hydrophilic carbon molecular sieve membrane (CMSM) comprising pores having a pore size of 0.25 nm to 0.55 nm for molecular sieving, and pores having a pore size of greater than 0.55 nm to 0.90 nm and a negligible amount of pores greater than 0.90 nm for adsorption diffusion, wherein the CMSM has a negligible amount of pores greater than 0.90 nm when a curve of N2 permeance versus permeation pressure at room temperature and 1 to 4 bar has a zero or negative slope; and
[0014] ii) humidifying the CMSM prepared in step i) to obtain water-saturated CMSM by:
[0015] treating it with water vapour at a temperature of 5°C to 180°C and at atmospheric pressure and a relative humidity above 95%, such as 99%, for a period of time such that after further treatment with water vapour, the permeate flux of a non-adsorbable gas such as N2 or He at 4 bar at the temperature at which the CMSM has been treated with water vapour is constant during a certain period of time, such as a period of 3 hours; or
[0016] - Optionally, exposing it to a water-saturated N2 or He gas stream by bubbling the gas into a water-filled tank at a temperature of 5°C to 180°C, so that after further exposure to the water-saturated N2 or He gas stream, the permeate flux of the non-adsorbable gas such as N2 or He is constant during a specific time period (such as a time period of 3 hours) at 4 bar and the above temperature.
[0017] The CMSM used in step i) comprises pores of a specific pore size as defined herein and a "defect-free structure", i.e. a structure that does not exhibit defects that could affect the gas separation properties of the membranes, i.e. their permeability and selectivity. A CMSM comprising pores of such a pore size is considered to be "defect-free" when the amount of pores greater than 0.90 nm is negligible, i.e. when the slope of the curve of N2 permeability versus permeation pressure at room temperature and at a pressure between 1 and 4 bar is zero or negative. The combination of these features, i.e. pores of said pore size and the absence of defects in the porous structure, allows obtaining the effect sought when humidifying the CMSM as defined in step ii).
[0018] Another aspect of the present invention relates to a method for preparing a water-saturated composite aluminum-carbon molecular sieve membrane (water-saturated Al-CMSM), comprising:
[0019] i) Preparation of hydrophilic Al-CMSM by:
[0020] -Providing a porous α-Al2O3 carrier;
[0021] - preparing a solution containing 5-20 wt% of phenolic resin, 0.5-5 wt% of formaldehyde, 0.1-2 wt% of ethylenediamine, and 0.1-5 wt% of boehmite in N-methyl-2-pyrrolidone, and heating the solution (e.g., 80 to 110° C. for 1 / 2 to 3 h) to perform a prepolymerization process to obtain a coating solution;
[0022] - impregnating the porous α-Al2O3 support with the coating solution to obtain a coated support;
[0023] - drying the coated support at a temperature of 70 to 120° C. in order to complete the polymerization process;
[0024] - carbonizing the dried coated support at a carbonization temperature of 450° C. to 750° C. in order to obtain Al-CMSM;
[0025] ii) humidifying the Al-CMSM prepared in step i) to obtain water-saturated Al-CMSM by:
[0026] treating it with water vapour at a temperature of 5°C to 180°C and at a relative humidity above 95%, such as 99%, at atmospheric pressure for a period of time such that after further treatment with water vapour, the permeate flux of a non-adsorbable gas such as N2 or He at 4 bar at the temperature at which the CMSM has been treated with water vapour is constant during a certain period of time, such as a period of 3 hours; or
[0027] - Optionally, exposing it to a water-saturated N2 or He gas stream by bubbling the gas into a water-filled tank at a temperature of 5°C to 180°C, so that after further exposure to the water-saturated N2 or He gas stream, the permeate flux of the non-adsorbable gas such as N2 or He is constant during a specific time period (such as a time period of 3 hours) at 4 bar and the above temperature.
[0028] Another aspect of the present invention is a water-saturated Al-CMSM obtainable by the above process.
[0029] Another aspect of the present invention relates to a method for separating a gas from a gas mixture, the method comprising:
[0030] a) providing a water-saturated membrane as defined above and below;
[0031] b) providing a gas mixture comprising at least two gases;
[0032] c) feeding the gas mixture into a water-saturated CMSM at a temperature ranging from 5°C to 300°C so as to obtain a retentate and a permeate, wherein the feeding is carried out at a pressure such that the partial pressure of the gas in the retentate is higher than the partial pressure of the gas in the permeate and such that the membrane remains a water-saturated membrane, i.e. a difference in permeation is observed compared to the same CMSM membrane not subjected to a humidification step so as to obtain a water-saturated membrane at the feed temperature and pressure.
[0033] Surprisingly, as shown in the examples, water-saturated CMSMs are not subject to external mass transfer limitations (concentration polarization) when processing gas mixtures. Thus, for example, in the separation of hydrogen present in a gas mixture, the correlation between the hydrogen partial pressure difference and the hydrogen flux is almost linear, independent of the H2 concentration in the mixture.
[0034] Another aspect of the invention relates to the use of a water-saturated CMSM as defined above and below for separating a gas from a gas mixture.
[0035] The inventors have also realised that a water-saturated CMSM as defined above and below can also be used for the dehydration of organic solvents and as a membrane reactor. These uses therefore also form part of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Shown are the micropore size distributions of carbon membranes carbonized under the following conditions: a) 450 and 650° C., b) 550 and 750° C. MS: molecular sieve region, AD: adsorption diffusion region.
[0037] Figure 2Depicted are the changes that occur on a CMSM: i) during carbonization, functional groups are removed, leaving active carbon groups that can react with reactive molecules; therefore, ii) water can be chemisorbed (i.e., reactive atoms react with water), generating oxygen-containing functional groups that render the pores hydrophilic; and then, iii) the hydrophilic groups can absorb water to physically fill the pores, thereby reducing the pore size.
[0038] Figure 3 Display (a, b) pressure difference is 400kPa, heating time is 0.7℃min -1 The penetration of N2 at .
[0039] Figure 4 a and 4b show the Figure 3 Polynomial fit derivatives of the fluxes of a and 3b.
[0040] Figure 5 The N2 and H2 permeabilities of Al-CMSM carbonized at 600 °C before and after humidification (outside the reactor) are shown.
[0041] Figure 6 The H2 and CH4 permeation results at 20°C for dried CMSM-550 and CMSM-600 membranes as obtained in Example 3 are shown along with the respective Robeson upper limit plots.
[0042] Figure 7 A comparison of hydrogen flow rate permeation of a 50% H2-50% CH4 mixture using a dry (after water desorption at 150°C) or humidified (wet) CMSM-550 membrane is shown. Permeation temperature: 20°C.
[0043] Figure 8 A comparison of the hydrogen purity of the permeate obtained by permeating a 50% H2-50% CH4 mixture using a dry (after desorption at 150°C) and a humidified (wet) CMSM-550 membrane is shown. Permeate temperature: 20°C.
[0044] Fig. 9 A comparison between the hydrogen flow rates of two H2-CH4 mixtures containing 10% and 50% hydrogen, respectively, at 20°C, 35°C, 50°C and 70°C in a humidified CMSM-550 membrane is shown.
[0045] Fig.10 A comparison between the hydrogen purity of the permeates obtained by permeating two H2-CH4 mixtures containing 10% and 50% hydrogen, respectively, at 20°C, 35°C, 50°C and 70°C using a humidified CMSM-550 membrane is shown.
[0046] Fig.11A comparison between the permeate hydrogen flow rates of two H2-CO2 mixtures containing 10% and 50% hydrogen, respectively, at 20°C, 35°C, and 50°C in a humidified CMSM-550 membrane is shown.
[0047] Fig.12 A comparison between the hydrogen purity of the permeates obtained by permeating two H2-CO2 mixtures containing 10% and 50% hydrogen, respectively, at 20°C, 35°C, 50°C and 70°C using a humidified CMSM-550 membrane is shown.
[0048] Fig.13 A comparison between the hydrogen flow rates of two H2-N2 mixtures containing 10% and 50% hydrogen, respectively, at 20°C, 35°C, 50°C and 70°C in a humidified CMSM-550 membrane is shown.
[0049] Fig.14 A comparison between the hydrogen purity of the permeates obtained by permeating two H2-N2 mixtures containing 10% and 50% hydrogen, respectively, at 20°C, 35°C, 50°C and 70°C using a humidified CMSM-550 membrane.
[0050] Fig.15 A comparison between hydrogen flow rates in H2-CH4 mixtures containing 10% hydrogen at 20°C, 50°C, 70°C and 100°C in dry and humidified CMSM-600 membranes is shown.
[0051] Fig.16 A comparison between the hydrogen purity of the permeates obtained using dry and humidified CMSM-600 membranes permeating a H2-CH4 mixture containing 10% hydrogen at 20°C, 50°C, 70°C and 100°C is shown.
[0052] Fig.17 The relative purity gains obtained under humidified membrane conditions are shown.
[0053] Fig.18 The flux dependence of Pd-based membranes (flux ≈ ΔP 0.5 ) and Al-CMSM (the flux is proportional to ΔP), considering that they have the same permeability (mol·m -2 s -1 ·Pa -1 ).
[0054] Fig.19 The hydrogen permeation flux of H2 / CH4 binary mixtures of 100-50% volume purity H2 at 400°C is shown as a function of the difference in the square root of the H2 partial pressure in the retentate (as an average) and the permeate side of the PdAg-supported membrane.
[0055] Fig. 20 Shown are the hydrogen flow rates at different hydrogen concentrations in the inlet mixture of H2-CH4 for the PdAg supported membrane tested at 400°C.
[0056] Fig.21 Shown are the hydrogen purities at different hydrogen concentrations in the inlet mixture of H2-CH4 for PdAg supported membranes tested at 400°C.
[0057] Fig. 22 The hydrogen flux is shown as a function of the hydrogen percentage in H2 / N2, H2 / CO2 and H2 / CH4 mixtures at 400°C, 3 bar total pressure and vacuum on the permeate side of the PdAg-supported membrane.
[0058] Fig.23 Shown is the hydrogen flow rate as a function of the hydrogen partial pressure difference for different H2 / CH4 mixtures at an operating temperature of 20°C when testing the CMSM-550 after exposure to ambient humidity.
[0059] Fig.24 Shown are: a) Schematic diagram of hydrophilic pores filled with water; b) water permeability of Al-CMSM of Example 2.2 carbonized at 550°C at various temperatures and pressures.
[0060] Fig.25 Shown is the water permeation of the Al-CMSM of Example 2.2 carbonized at different temperatures and a pressure difference of 3 bar.
[0061] Fig.26 The water-gas selectivity for various gases as a function of the permeation temperature of the Al-CMSM of Example 2.2 carbonized at different temperatures is shown. DETAILED DESCRIPTION
[0062] Unless otherwise stated, all terms used in this application should be understood according to their common meanings known in the art. Other more specific limiting terms used in this application are as follows and are intended to be uniformly applied throughout the specification and claims, unless otherwise explicitly stated to provide a broader definition.
[0063] The term "permeate flow" is defined as the volume of gas passing through a membrane per unit time. This value is determined experimentally using a soap flow meter.
[0064] The term "permeate flux" is defined as the volume flowing through a membrane per unit area per unit time. This value is calculated by dividing the "permeate flow rate" by the membrane area.
[0065] The term "permeability" is defined as the volume of gas passing through a unit membrane area per unit time and unit pressure gradient. The common unit used in CMSM is mol·m -2 s -1 ·Pa -1 This value is calculated by dividing the "Permeate Flux" by the pressure difference between the retentate and the permeate.
[0066] The term "permeability" is defined as the flux of material transport through a membrane per unit of membrane thickness per unit of driving force.
[0067] The term "perm selectivity" or ideal selectivity as it relates to gases refers to the ratio of the permeabilities of two gases at the same temperature.
[0068] The term "composite alumina-carbon molecular sieve membrane" or "Al-CMSM" refers to a carbon membrane having alumina nanoparticles dispersed in a carbon matrix.
[0069] The term "water-saturated CMSM" or "hydrated CMSM" refers to a CMSM (including supported Al-CMSM) containing an amount of water corresponding to the amount of water contained in a CMSM that has been treated with water vapor at a temperature of 5°C to 180°C (such as at room temperature), at atmospheric pressure and a relative humidity of more than 95% (such as 99%) for a certain period of time, such that after further treatment with water vapor, the permeate flux of non-adsorbable gases (such as N2 or He) is constant at 4 bar at the temperature at which the CMSM has been treated with water vapor for a specific period of time (such as a period of 3 hours). Alternatively, the "water-saturated CMSM" can be obtained by exposing the CMSM to a water-saturated N2 or He gas stream by bubbling the gas into a tank filled with water at a temperature of 5°C to 180°C (such as at room temperature), such that after further exposure to the water-saturated N2 or He gas stream, the permeate flux of non-adsorbable gases (such as N2 or He) at 4 bar and the temperature is constant for a specific period of time (such as a period of 3 hours).
[0070] Typically, in particular at temperatures above 180°C, a water-saturated CMSM is one that contains at least an amount of water that corresponds to the amount of water that would be contained in a CMSM that has been subjected to a humidification treatment at a temperature and pressure at which permeation would occur so as to fill the pores with water until no more water remains, resulting in a permeation difference being observed due to the presence of water in the pores compared to the same CMSM that has not been subjected to such a humidification treatment.
[0071] The term "hydrophilic CMSM" refers to a CMSM that has a N2 permeability higher than 7 × 10-7 at 300 °C and 4 bar differential pressure before being humidified to obtain a water-saturated CMSM. -9 mol m 2 s-1 Pa -1 , and after being humidified to obtain a water-saturated CMSM, the N2 permeability at room temperature and a pressure difference of 1 bar is less than 1×10 -9 mol m 2 s -1 Pa -1 .
[0072] Membrane processes are characterized by the fact that the feed stream, which is a gas mixture, is separated into two streams: the retentate and the permeate. The retentate is the portion of the feed that does not pass through the membrane, while the permeate is the portion of the feed that does pass through the membrane, i.e. the separated gas. In order to separate a gas from a gas mixture, the partial pressure of the gas in the retentate should be higher than the pressure of the permeate.
[0073] Therefore, the permeation of the desired gas will depend on the difference in partial pressure of the gas in the retentate and the permeate. For example, for a feed of a 10% H2 and 90% CH4 mixture, if the pressure in the permeate is atmospheric pressure (1 bar), the pressure in the feed must be above 10 bar, i.e., the partial pressure of H2 in the feed must be above 1 bar.
[0074] The term "pressure differential" refers to the difference between the gas pressure in the retentate and the gas pressure in the permeate.
[0075] The term "differential partial pressure" of a given gas refers to the difference between the partial pressure of the gas in the retentate and the partial pressure of the gas in the permeate.
[0076] The term "negligible" means a value that is consistent with zero within the measurement accuracy or is less than a defined threshold, which for example takes into account deviations from zero that are hardly avoidable for structural reasons or do not have any significant effect on the performance of the CMSM in terms of permeability and selectivity. In order to verify whether a CMSM has a "negligible amount of pores larger than 0.90 nm", i.e. whether it has a defect-free structure, the CMSM must be able to present a curve of N2 permeability versus permeation pressure with a slope of zero or negative at room temperature and a pressure of 1 to 4 bar.
[0077] The term "room temperature" refers to a temperature of about 20°C to about 25°C.
[0078] As used herein, the term "atmospheric pressure" is intended to refer to substantially atmospheric pressure of 101.325 kPa (ie, 760 mm Hg) ± 15 kPa.
[0079] As used herein, the term "%" or "concentration" of a gas component in a gas mixture refers to the amount by volume of a single gas component relative to the total volume of the gas mixture, or (if specifically mentioned) the total volume of one or more other gas components in the gas mixture.
[0080] It is noted that, as used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.
[0081] As stated above, the present invention relates to water-saturated carbon molecules as defined above.
[0082] These carbon membranes exhibit a porous structure in which the permeation mechanism is the result of molecular sieving (pore range 0.25-0.55 nm) and / or surface diffusion (0.5-0.90 nm). CMSM (such as Al-CMSM) is produced by carbonization of polymer precursors under an inert atmosphere or vacuum, such as at a temperature of 250°C to 2500°C, or 450°C to 1500°C, especially 500°C to 800°C (see Llosa MA et al. (Part I) 2015; Campo MC et al. 2010). Examples of polymer precursors include, but are not limited to, polyimides, polyfurfuryl alcohol, phenolic resins, cellulose, cellulose derivatives, and poly(vinylidene chloride). Phenolic resins, such as resols and novolacs, are desirable precursors for preparing CMSM because they offer the advantages of low price and high carbon yield and withstanding high temperatures without deformation.
[0083] Phenolic resins are products of the polycondensation of phenol and formaldehyde; their structure and properties depend on the formaldehyde / phenol ratio (F / P), catalyst, pH and temperature. There are two forms of phenolic resins: resols and novolacs. Resols are products of alkaline catalysis in excess of formaldehyde (F / P>1). Novolacs are obtained in an acidic medium and have a low formaldehyde content, typically with an F / P of about 0.75-0.85.
[0084] In one embodiment of the method for preparing a water-saturated Al-CMSM and the water-saturated Al-CMSM obtainable by the method of the present disclosure, the phenolic resin is a novolac resin.
[0085] In another embodiment of the method for preparing water-saturated Al-CMSM of the present disclosure and the water-saturated Al-CMSM obtainable by the method, optionally in combination with one or more features of the specific embodiments defined above, the carbonization temperature is 450°C to 700°C, in particular 500°C to 650°C, such as 550°C or 600°C.
[0086] Prior to carbonization, for self-supported membranes, the polymer precursors are shaped (e.g., thin films, hollow fibers); for supported membranes, they are usually produced by impregnating (coating) a porous support with a solution containing the polymer precursors.
[0087] As described above, the membrane is humidified so as to obtain a CMSM containing at least an amount of water corresponding to the amount of water containing a CMSM that has been subjected to:
[0088] - treated with water vapour at a temperature of 5°C to 180°C (such as 20°C, 25°C, 40°C, 70°C, 100°C or 120°C), atmospheric pressure and a relative humidity above 95%, in particular 99%, for a period of time such that after further treatment with water vapour, the gas permeate flux of the membrane that does not adsorb gases (such as N2 or He) is constant during a certain period of time (such as a period of 3 hours) at the temperature at which the CMSM has been treated with water vapour and at 4 bar, or
[0089] - exposing it to a gas stream saturated with water by bubbling the gas into a tank filled with water at a temperature of 5°C to 180°C (such as 20°C, 25°C, 40°C, 70°C, 100°C or 120°C) so that after further exposure to the water-saturated gas stream, the permeate flux of the non-adsorbable gas (such as N2 or He) is constant during a specific period of time (such as a period of 3 hours) at 4 bar and the above temperature.
[0090] At the above temperature and pressure, the permeate flux was measured using a soap bubble flow meter.
[0091] In another embodiment of the water-saturated carbon molecular sieve membrane of the present invention, optionally in combination with one or more features of the specific embodiments defined above, the membrane is humidified at a temperature above 180°C (such as 200°C, 250°C or 300°C) to obtain a CMSM containing at least a certain amount of water, which is equivalent to the amount of water that would be contained in such a CMSM, which has been humidified at the temperature and pressure at which permeation is carried out so as to fill the pores with water until no more water remains, thereby observing a permeation difference due to the presence of water in the pores compared to the same CMSM that has not been subjected to such humidification treatment.
[0092] In one embodiment, humidification of the membrane is performed at room temperature, atmospheric pressure and a relative humidity above 95% (such as 99%) for a certain period of time, so that after further treatment with water vapor, the gas permeation flux of the membrane for non-adsorbable gases such as N2 or He is constant during a specific period of time (such as a period of 3 hours) at the temperature and 4 bar at which the CMSM has been treated with water vapor.
[0093] In one embodiment of the water-saturated carbon molecular sieve membrane of the present invention, optionally in combination with one or more features of the above-mentioned specific embodiments, the CMSM is a composite alumina-carbon molecular sieve membrane (Al-CMSM). In particular, relative to the total weight of the membrane, the Al-CMSM has a nitrogen content of 0.1 wt% to 4.0 wt%, an alumina content of 2.5 wt% to 50 wt% and a carbon content of 50 wt% to 95 wt%.
[0094] Al-CMSM can be prepared using the material on a porous alumina support and a once-impregnation-drying-carbonization method described by Llosa MA et al. (Part I) 2015 (see the experimental section on page 5655), but the carbonization temperature is arbitrarily selected. Other examples of Al-CMSM are disclosed, for example, in Teixeira et al. 2011, Teixeira et al. 2012, Rodrigues et al. 2014.
[0095] Pore size characterization
[0096] The pore size and pore size distribution of the carbon molecular sieve membranes were calculated using data obtained from the adsorption equilibrium of CO2 at 0°C. The adsorption equilibrium isotherm of CO2 was obtained gravimetrically on a Rubotherm suspension magnetic balance with an accuracy of 10 -5 Detailed information on how to determine the pore size distribution of CMSM can be found in Nguyen C. and Do, DD 1999 and Nguyen C., et al. 2003.
[0097] Water vapor pretreatment of the membrane can be performed inside or outside the permeator to obtain a water-saturated CMSM.
[0098] Water vapor pretreatment outside the permeator
[0099] In order to obtain a water-saturated CMSM, the hydrophilic CMSM as defined above is introduced into a closed container in which water is present at a temperature of 5 to 180° C., such as 5 to 120° C., in particular at room temperature, and a relative humidity of greater than 95% (99%), until no more water remains, so as to fill the pores with water.
[0100] In order to know when the membrane is saturated with water, the gas permeation flux of the membrane at the temperature (such as room temperature) and 4 bar is monitored until it is constant during a certain period of time (such as a period of 3 hours). The gas used is a non-adsorbable gas at the permeation temperature (e.g., room temperature), such as N2 or He.
[0101] Water vapor pretreatment inside the permeator
[0102] As an alternative method to obtain water-saturated CMSM, the CMSM is introduced into the permeator and fed to the permeator, preferably at room temperature: (i) a gas stream saturated with water, for example, obtained by bubbling a gas stream into a tank filled with water before feeding it to the permeator; or (ii) water vapor or a mixture of water-containing gases. The treatment time can range from 1 minute to several hours.
[0103] After treatment, the gas flux of non-adsorbable gas (i.e., N2 or He) at 4 bar was measured. The treatment and gas permeation cycles were repeated until the gas permeation was constant over a period of 3 hours.
[0104] Use of the water-saturated CMSM of the present invention
[0105] As mentioned above, the present invention also relates to a method for separating gases in a gas mixture by using a water-saturated CMSM as defined above having some specific characteristics.
[0106] Therefore, a CMSM with some specific characteristics such as pore size, pore size distribution and hydrophilicity is pre-treated by humidification until it is saturated with water (under permeation conditions of pressure and temperature). The gas mixture contains at least two gases and is fed to the water-saturated CMSM at a certain pressure so that the partial pressure of the gas in the retentate is higher than the partial pressure of the gas in the permeate and the membrane is still a water-saturated membrane, that is, a permeation difference is observed compared to the same CMSM without a humidification step to obtain a water-saturated membrane at the feed temperature and pressure. The process can be carried out at a temperature of 5°C to 300°C.
[0107] In one embodiment, optionally in combination with one or more features of the specific embodiments defined above, step (c) is carried out at a temperature of 5° C. to 250° C., 5° C. to 120° C., 15° C. to 120° C., 15° C. to 100° C., 15° C. to 70° C. or 20° C. to 50° C., such as 40° C. In a specific embodiment, step (c) is carried out at room temperature.
[0108] The gas in the form of pure gas or mixture can be fed to the permeator by a digital mass flow controller, while the pressure can be controlled using a digital back pressure regulator. The maximum retentate pressure can be, for example, 40 bar, while the permeate can be operated at different pressures down to vacuum (using a vacuum pump). Several thermocouples can be used to record the temperature distribution along the permeator.
[0109] Gas separation in hydrophilic membranes of the present disclosure is based on molecular sieving (MS; gases smaller than the pores will permeate) and adsorptive diffusion (AD; differences in the affinity of the gas for the water present in the pores). The pores of the CMSM of the present disclosure are divided into two groups ( Figure 1a): pores from 0.25nm to 0.55nm, where separation occurs by molecular sieving, and b) pores with pore sizes greater than 0.55nm to 0.90nm, where water is adsorbed. In the AD region, water adsorbed in the pores causes the pore size to decrease; the amount of water adsorbed depends on the temperature and therefore the pore size. Gases will pass through according to their size (the smallest will pass faster), and gases that interact (adsorb) more with the water in the pores (more adsorbed gases) will permeate preferentially. The interaction with water will depend on the polarity of the gas, and gases with a dipole moment (i.e., water) will have more permeation. When the gas is not polar, gases with higher polarizability will permeate faster (e.g., CO2 and H2 over He).
[0110] <![CDATA[Polarizability [m 3 > Kinetic diameter [nm] He 2 0.26 <![CDATA[H2]]> 8.2 0.29 <![CDATA[CO2]]> 26.3 0.33 Ar 16.6 0.364 <![CDATA[N2]]> 17.7 0.365 <![CDATA[CH4]]> 26 0.38
[0111] The polarizability of an atom or molecule is a measure of the ease with which electrons and nuclei can be displaced from their average position to form a momentary dipole. The kinetic diameter represents the probability that a molecule in a gas will collide with another molecule. It indicates the size of the molecule being targeted. The polarizability and kinetic diameter of a gas can be found in chemical and physical data handbooks.
[0112] In another embodiment, optionally in combination with one or more features of the specific embodiments defined above, at least two gases have a polarizability of 2 to 27 or 2 to 26.3, and at least one of the at least two gases has a kinetic diameter of less than 0.55 nm. If the kinetic diameters of more than two gases are less than 0.55 nm, separation occurs if: the difference in kinetic diameter between at least two gases is equal to or greater than 0.01 nm; the difference in polarizability between at least two gases is equal to or greater than 1 nm. 3 ; or both.
[0113] In particular, the at least two gases are selected from He, H2O, Ne, H2, NO, Ar, NH3, N2, O2, CO2, CO, CH4, C2H4, C2H6, propylene, C3H8 (propane), H2S, methanol, ethanol, propanol, dihydrogen sulfide, ethanol, propanol, propylene, propane ... propylene, propane, propylene, propylene, propylene, propylene, propylene, propylene, propylene, propylene, propylene, propylene, propylene, propylene, propylene, propylene, propylene, propylene, propylene, Examples of gases with a kinetic diameter greater than 0.55 nm are n-butane or isobutane. Examples of solvents with a kinetic diameter greater than 0.55 nm are CHCl3, CHCl2, methanol, ethanol, dimethyl ether, dimethyl carbonate, acetone, acetonitrile, dimethyl ether, dimethyl carbonate, dimethyl ether ... In particular, the at least two gases are selected from a mixture of H2 / CH4; H2 / N2; H2 / CO2; CO2 / CH4; CO2 / N2; O2 / N2; and biogas.
[0114] In a specific embodiment, optionally in combination with one or more features of the specific embodiments defined above, the gas mixture comprises 5% to 20% H2 and 95% to 80% CH4, in particular about 10% H2 and about 90% CH4, and wherein step c) is carried out at a hydrogen partial pressure difference equal to or higher than 3 bar, such as 3 bar to 8 bar, and at a temperature of 40°C or lower, such as 20°C or room temperature.
[0115] Advantageously, unlike other known methods, the water-saturated CMSM of the present invention allows separation of H 2 from a mixture with CH 4 at low temperatures, thus increasing the purity of the permeate.
[0116] In a particular embodiment, optionally in combination with one or more features of the particular embodiments defined above, at least two gases are CO2 and N2. In particular, the gas mixture comprises 10% to 20% CO2 and 65% to 75% N2, in particular about 15% CO2 and about 70% N2.
[0117] In a particular embodiment, optionally in combination with one or more features of the particular embodiments defined above, at least two gases are H2 and CO2. In particular, the gas mixture comprises 55% to 65% H2 and 30% to 40% CO2, more particularly about 60% H2 and about 35% CO2.
[0118] In another embodiment, optionally in combination with one or more features of the specific embodiments defined above, the gas mixture is anhydrous.
[0119] In another embodiment, optionally in combination with one or more features of the specific embodiments defined above, the gas mixture comprising at least two gases is biogas and the CO 2 is removed from the biogas.
[0120] As mentioned above, another aspect of the invention relates to the use of a water-saturated CMSM as defined above for separating a gas from a gas mixture.
[0121] Biogas is a gas mixture produced by the decomposition of organic matter in the absence of oxygen (anaerobic), which includes methane and carbon dioxide. In particular, biogas is a gas mixture that contains mainly methane and carbon dioxide and small amounts of other gases such as H2, H2S, N2 and water vapor. The use of biomethane is superior to biogas because the energy density of the fuel source is increased and it can be used directly in all existing and installed plants and can also be delivered to the natural gas grid.
[0122] In another embodiment, the use of the water-saturated CMSM is for biogas upgrading, ie, removing CO 2 from biogas.
[0123] In another embodiment, the use of the water-saturated CMSM is to remove CO2 from a gas mixture containing at least 50% nitrogen. In particular, the gas mixture contains 5% to 10% CO2 and 65% to 75% N2, more particularly about 5% CO2 and about 70% N2.
[0124] In another embodiment, the use of the water-saturated CMSM is for separating H2 from a gas mixture further comprising CO2, in particular for separating H2 from a precombustion product after a water-gas shift reaction, wherein the gas mixture comprises 50% to 70% H2 and 50% to 30% CO2; or for separating alkanes from olefins, such as, for example, separating C2H4 from C2H6 in a gas mixture comprising 30-70% C2H4 and 70-30% C2H6; or, for example, separating propane from propylene in a gas mixture comprising 30-70% propylene and 70-30% propane; or, for example, separating propane, propylene or a mixture thereof from butane in a gas mixture comprising 70-30% propane, propylene or a mixture thereof and 30-70% butane.
[0125] As mentioned above, another aspect of the present invention relates to the use of a water-saturated CMSM as defined above for solvent dehydration, i.e., for removing water from an organic solvent to obtain an organic solvent containing 0.1 to 1% water. Examples of organic solvents include methanol, ethanol, propanol, n-butanol, isobutanol, tert-butanol, acetone, dimethyl ether, dimethyl carbonate, tetrahydrofuran, acetonitrile, dimethyl ether, dimethyl carbonate ... ether, dimethyl carbonate, dimethyl ether, dimethyl ether, dimethyl ether, dimethyl ether, dimethyl ether, dimethyl ether, dimethyl ether, dimethyl ether, dimethyl ether, dimethyl ether, dimethyl ether, dimethyl Alkane, acetic acid and ethyl acetate.
[0126] During solvent dehydration, water vapor is forced through the pores by applying a vacuum from the permeate side of the membrane. Since the solvent molecules are large or close to the largest pores of the molecular sieve (>0.55 nm), and water is very small, only water will pass through. In addition, water is preferentially adsorbed in the hydrophilic pores of the AD region, which blocks the passage of other less hydrophilic molecules. Dipolar aprotic solvents are used in organic synthesis and dissolution of polymers, where very small or trace amounts of water may be harmful.
[0127] As mentioned above, another aspect of the present invention relates to the use of a water-saturated CMSM as defined above as a membrane reactor. The water-saturated CMSM of the present invention can be used for process intensification for in-situ removal of water during catalytic reactions in the chemical, petrochemical, food, and cosmetic sectors. In particular, in the production of methane, methanol, dimethyl ether, dimethyl carbonate (DMC) or other organic solvents in which water is produced in the reaction. Examples of methods in which the water-saturated CMSM of the present invention can be used as a membrane reactor are the reaction of CO2 and H2 to produce CH4; the synthesis of esters by the reaction of alcohols with carboxylic acids; biodiesel and biolubricants; methanol produced from CO2 and H2; dimethyl ether obtained by dehydration of methanol or direct synthesis from CO2 and H2; and the synthesis of dimethyl carbonate from CO2 and methanol. By using the water-saturated CMSM of the present invention, water is removed from the production of reaction products and compounds of interest (such as oxygenated solvents and esters).
[0128] The water-saturated CMSMs of the present invention have great potential because they are easier to prepare, cheaper and have better permeability than the zeolite membranes currently studied in the field of membrane reactors, especially for the reaction of CO2 and H2.
[0129] As mentioned above, one aspect of the present invention relates to a method for preparing a water-saturated Al-CMSM as defined above. The water-saturated Al-CMSM obtainable by the above method also forms part of the present invention.
[0130] Therefore, the method of separating a gas from a gas mixture of the present invention can also be defined by comprising the following steps:
[0131] a) providing a water-saturated Al-CMSM as defined above;
[0132] b) providing a gas mixture comprising at least two gases as defined above;
[0133] c) feeding the gas mixture to the water-saturated Al-CMSM at a temperature of 5° C. to 300° C., in particular 5° C. to 250° C., to obtain a retentate and a permeate, wherein the feeding is carried out at a pressure such that the partial pressure of the gas in the retentate is higher than the partial pressure of the gas in the permeate.
[0134] Throughout the specification and claims, the word "comprise" and variations of the word are not intended to exclude other technical features, additives, components or steps. In addition, the word "comprises" covers the situation of "consisting of..." Other objects, advantages and features of the present invention will become apparent to those skilled in the art after examining this specification, or can be understood by the practice of the present invention. The following examples and drawings are provided in an illustrative manner, and they are not intended to limit the present invention. In addition, the present invention covers all possible combinations of specific and preferred embodiments described herein.
[0135] Example
[0136] Example 1. Membrane preparation
[0137] Several Al-CMSMs were prepared on porous alumina supports using the materials and once-impregnation-drying-carbonization method described in Llosa MA et al. (Part I) (see the experimental section on page 5655), except for the carbonization temperature. In particular, the document discloses the preparation of Al-CMSMs by carbonizing the membrane at 500° C. Likewise, Al-CMSMs were prepared by carbonization at 500, 550, 600, 650, 750, 850, and 1000° C.
[0138] Since the permeation depends on the storage humidity and time (change in the amount of water in the pores), the effectiveness of pre-treating the Al-CMSM with water vapor was demonstrated by comparing it with the performance of a "dry membrane" obtained by removing most of the water present in the pores through thermal treatment. The water-saturated Al-CMSM after pre-treatment with water vapor will be referred to as a "humidified membrane".
[0139] Pore size distribution
[0140] Figure 1The micropore size distribution of membranes carbonized at different temperatures is presented. The membranes show the presence of ultramicropores (0.25-0.55 nm range, MS region) and larger micropores (0.55 nm-0.90 nm, AD region). The membrane carbonized at 450 ° C has a smaller pore volume in which the pores are in the range of 0.4 to 0.90 nm; the membrane carbonized at 550 ° C has a similar pore size distribution pattern, but with significantly larger pore volume. When carbonized at 650 ° C, the bidisperse pore size distribution has a significantly larger volume in the MS range (0.25 to 0.55 nm; in the AD region, most of the pores are in the range of greater than 0.55 to 0.65 nm), which can well balance selectivity and permeability. Finally, compared with 650 ° C, the 750 ° C sample shows a smaller volume in the MS region and a larger volume in the AD region, with a very clear pore size distribution, which can contribute to higher permeability. These results show that the volume and number of smaller micropores increase with increasing carbonization temperature up to 650 °C, and larger pores are formed at higher carbonization temperatures.
[0141] Penetration Testing
[0142] The permeability of gases through the loaded CMSM was measured using a shell and tube instrument equipped with a back pressure regulator (lower limit <20 kPa) and a bubble flow meter (detection limit <0.2 ml / min). The selected gas was introduced into the membrane tube from the housing, and the gas permeating through the membrane was introduced into the bubble flow meter to determine the rate. Gas permeation to N2 was measured at room temperature (unless otherwise stated) and at different pressures, while the permeate side was at atmospheric pressure.
[0143] Hydrophilicity and water adsorption in pores
[0144] Just after carbonization and avoiding contact with air, the N2 permeance of the membranes was measured.
[0145] like Figure 2 As shown, during carbonization, functional groups are removed, leaving active carbon groups that can react with active molecules; therefore, water can be chemically adsorbed, generating oxygen-containing functional groups that make the pores hydrophilic. The hydrophilic groups can then absorb water to physically fill the pores, thereby reducing the pore size.
[0146] The water desorption of membranes carbonized at different temperatures was studied by measuring the N2 permeability as a function of permeation temperature at a pressure difference of 400 kPa. Figure 3 a and Figure 3 b) In Figure 3 In a, it can be observed that the N2 flux increases as the carbonization temperature of the membrane increases from 450°C to 600°C. At 450°C, the N2 flux is low and has no maximum value, which indicates that the carbonization temperature is low and few pores are formed. Figure 3 a and Figure 3 The derivative curves of permeation flux and temperature of b are presented in Figure 4 a and Figure 4 b. With increasing carbonization temperature, the intensity of the derivative and the permeation temperature corresponding to the maximum increase; the maximum shifts with the carbonization temperature; for carbonization temperatures of 500, 550, and 600 °C, the maximum temperatures are 150 °C, 175 °C, and 280 °C, respectively. This behavior is related to the strength of the interaction between water and the pores. At 750 °C and 850 °C, the N2 permeance is lower and no maximum is observed; at these temperatures, the pores become less hydrophilic. It can be inferred that in the carbonization temperatures tested at approximately 600-650 °C, the membrane has the highest hydrophilicity, trapping more water in the pores.
[0147] For the membranes carbonized at 500 °C, the system was cooled down to room temperature and without removing the membrane from the permeation reactor, a boat containing water was introduced and the N2 permeance at 400 kPa was recorded as a function of time. At the beginning of the experiment, a sharp drop in permeability was observed; water was adsorbed in the most accessible places of the membrane. The adsorption was rapid for the first 20 minutes, after which a gradual small drop in permeability was observed; water was adsorbed in the inner pores of the membrane. Therefore, Figure 3 The increase in nitrogen permeation with increasing temperature is the result of the gradual removal of water from the pores. The same membrane was treated again at 300°C under nitrogen to remove physically adsorbed water from the pores, and the N2 permeance was measured over time as explained above, but this time, a boat containing hexane was introduced into the reactor. The N2 permeance remained constant; this clearly indicates that the pores of the membrane are hydrophilic (i.e., hexane is hydrophobic and is not adsorbed by the pores).
[0148] Example 2. Steam pretreatment of Al-CMSM outside the permeator
[0149] 2.1 Drying film
[0150] The Al-CMSM carbonized at 500 °C was heated at 200 °C under N2 to remove the adsorbed water from the pores.
[0151] 2.2 Humidification membrane
[0152] The dried Al-CMSM prepared as disclosed above is taken out from the permeator and hydrated (pre-treated with water vapor outside the permeator) by placing the membrane in a box containing water at room temperature, atmospheric pressure and relative humidity above 95%, such as 99%, until saturation with water is reached (humidifying the membrane).
[0153] 2.3 N 2 Penetration testing with H2
[0154] The permeability of N2 and H2 was performed before and after humidification of Al-CMSM as disclosed in Example 2 but carbonized at 600°C. The effect of hydration is clear: the permeability of both N2 and H2 is significantly reduced (see Figure 5 ). However, the permeability reduction for N2 is greater than for H2, which is reflected in the selectivity for H2; thus, the ideal permeability selectivity for H2 / N2 at 1 bar for the humidified membrane is 70 times higher than that for the membrane without humidification.
[0155] Example 3. Steam pretreatment of Al-CMSM inside the permeator
[0156] Two carbon molecular sieve membranes were prepared as disclosed in Example 2, but at carbonization at 550° C. and 600° C. They are referred to as CMSM-550 and CMSM-600, respectively.
[0157] 3.1 Drying film
[0158] The CMSM-550 and CMSM-600 membranes were placed inside the permeator. Then, nitrogen was introduced into the permeator, and the temperature was raised to 150° C. at a heating rate of 2° C. / min. The above temperature was maintained for 6 hours to obtain the corresponding dehydration membranes.
[0159] After desorption of water from the pores, the membranes were cooled to the permeation temperature (ie, 20 to 100° C.) and permeability studies of the dried membranes were performed.
[0160] 3.2 Humidification membrane
[0161] The dried membrane obtained above was exposed to a water-saturated N2 gas stream by bubbling the gas into a tank filled with water at room temperature, which was then fed to the permeator. In order to guarantee the same humidification throughout, the membrane was saturated with water from the humidification stream every night for 12 hours before the experiment was performed. A nitrogen pure gas permeation test was performed to confirm that the nitrogen permeation at 4 bar pressure was constant.
[0162] Example 4. Permeation studies of dry and humidified membranes
[0163] Permeation of pure hydrogen and hydrogen-containing gas mixtures was performed and the hydrogen permeation and purity values were measured at different pressures and temperatures. A vacuum was applied on the permeate side.
[0164] In terms of wet membranes, the first interesting result is the superior selectivity and permeability compared to the Robeson cap, e.g. Figure 6 This limit provides a reference against which new membrane materials can be compared.
[0165] The differences in hydrogen flow rate and purity in Al-CMSM (CMSM-550) carbonized at 550°C before (drying) and after (humidifying) water vapor treatment (humidification) of a gas mixture containing 50% hydrogen and 50% methane at 20°C and various hydrogen partial pressure differences are shown in Figure 7 and 8 Without wishing to be bound by theory, it is believed that the water treatment wets the walls of the pores with water, thus reducing the pore size (pore filling). The results show that although the hydrogen flux is reduced ( Figure 7 ), but the purity of hydrogen is significantly improved ( Figure 8 ).
[0166] Example 5. Permeation of a gas mixture using an Al-CMSM-550 humidification membrane
[0167] Using the procedure described in Section 3.2 of Example 3, the CMSM-550 was pretreated with a gas stream of N2 saturated with water vapor and used to measure the hydrogen permeation and permeate purity of binary mixtures of hydrogen with CH4, CO2 or N2 with 10% or 50% hydrogen at various temperatures (20°C to 70°C) and various partial pressure differences, with vacuum applied from the permeate side.
[0168] The separation of hydrogen present in a mixture with methane containing 10% and 50% hydrogen was studied using the CMSM-550 membrane. Fig. 9 The hydrogen flux rates in the permeate obtained from a mixture of H2 and CH4 (10% and 50% H2) at different temperatures and H2 partial pressure differences are shown in FIG. Fig.10 The corresponding H2 purity is shown. It can be observed that with increasing permeation temperature, the hydrogen permeability increases, but at the expense of hydrogen purity. It is important to highlight that for carbon membranes saturated with water vapor, the hydrogen purity obtained is very high, especially when taking into account the 10% H2 content in the mixture. Thus, in particular, at 20°C and a hydrogen partial pressure of 0.55 bar, a purity of 97.5% is obtained.
[0169] Similar tests were performed with binary mixtures of hydrogen and either N2 or CO2. For CO2, the results show Fig.11 and 12 and for N2, the results are shown in Fig.13 and 14 middle.
[0170] For the separation of H2 from a mixture with CO2, the permeate purity is lower than that of a mixture with CH4, probably because CO2 is smaller and more easily absorbed than CH4 ( Fig.12 ).
[0171] exist Fig.13 and 14In Figure 1, the results for H2-N2 in terms of hydrogen flow rate and purity are plotted at different hydrogen partial pressure differences. When the membrane is saturated with water, high hydrogen purity is achieved with all the different mixtures considered. At higher temperatures, such as 100°C, a real improvement in performance is expected when the membrane is humidified.
[0172] For gases with significantly different molecular sizes or very different adsorption capacities, such as CO2 / CH4 or CO2 / N2, similar results (to those obtained with H2 / N2, H2 / CH4 and H2 / CO2) are expected. Due to their high water adsorption capacity, membranes carbonized at 500°C to 750°C, in particular 500°C to 700°C, will behave in a similar manner when tested under humidified conditions with dry gas. When performed with the corresponding humidified membranes, high selectivity and purity are expected to be achieved at operating temperatures up to 100°C.
[0173] Thus, similarly, humidified Al-CMSM carbonized at 500°C was used to purify hydrogen from a mixture containing 10% H2 and 90% N2. This separation is important because existing natural gas infrastructure can be used to store and distribute hydrogen. For safety reasons, low concentrations of H2 (i.e., 10%) can be mixed; a strong dependence of purity on the permeation temperature was observed. In particular, at 30°C, a hydrogen purity of 99.4% was obtained.
[0174] Example 6. Difference in hydrogen permeation performance between dry and humidified CMSM-600 membranes
[0175] The dried CMSM-600 membrane was obtained by heating the membrane at 150°C under a nitrogen atmosphere inside the permeator (most of the water was removed from the pores). The temperature of the permeator was then cooled to 100°C and hydrogen permeation of a mixture of 10% H2 and 90% CH4 was performed at different hydrogen partial pressures (100°C dried membrane).
[0176] Then, the same gas mixture was saturated with water by bubbling in water for 15 hours and then entered the permeator at 100°C. In this way, water was selectively adsorbed in the hydrophilic (humidified) membrane at 100°C and hydrogen permeation was performed at various hydrogen partial pressures (100°C humidified membrane). The same procedure was performed at different temperatures: 70°C, 50°C and 20°C.
[0177] Through the humidified membrane, the hydrogen flow rate decreases ( Fig.15 ), resulting in a significant increase in purity ( Fig.16 This is more pronounced at higher temperatures. The average increase in purity after humidification of the membrane (wet versus dry) is 18% at 100°C, 14% at 70°C, 10% at 50°C, and only 4% at 20°C ( Fig.17). This indicates that at temperatures above 100 °C, it will be more important to pre-treat the carbon membrane with a water vapor flow.
[0178] Therefore, according to the above results, the humidified membrane gives excellent advantages for purification especially at higher temperatures.
[0179] Comparative Example 1. Comparison between Pd-based film and Al-CMSM
[0180] Pd-based membranes are used for hydrogen separation due to their high hydrogen permeability and unique selectivity. The permeation is preferably performed at 400°C because they may be damaged at temperatures below 300°C and above 500°C.
[0181] In Pd-based membranes, the hydrogen flux is a function of the square root difference in the partial pressure difference across the membrane (Sievert's law). In Al-CMSM, the flux is proportional to the partial pressure difference.
[0182] Fig.18 An example of the pressure dependence of the hydrogen flux for a Pd-based membrane and an Al-CMSM humidified in a reactor until saturated with water is shown, considering that both have the same permeability at a pressure difference of 1 bar. It can be observed that at low pressures, the flux is similar in both cases. However, as the pressure increases, the permeation gain of the Al-CMSM is much higher than that of the Pd-based membrane. At low pressures, the H2 permeation of the Al-CMSM is about 10 times lower than that of a Pd-based membrane of the same thickness; the selectivity of the Al-CMSM is also lower (actually 20-40 times lower than that of a Pd-based membrane), however, the permeation of the Al-CMSM can be carried out at low temperatures (i.e., room temperature), while the Pd membrane is carried out at high temperatures (typically 400°C).
[0183] Comparative Example 2. Effect of Hydrogen Concentration in Mixtures with Other Gases on Hydrogen Permeation
[0184] exist Fig.19In, the hydrogen permeation flux of pure hydrogen and various H2 / CH4 binary mixtures (100% to 50% hydrogen) at 400°C for a 1.29 μm thick PdAg supported membrane is plotted as a function of the square root difference in hydrogen partial pressure (see Melendez, J. et al., "Preparation and characterization of ceramic supported ultra-thin (~1 μm) Pd-Ag membranes", J. Memb. Sci. 528 (2017), pp. 12–23). Pure hydrogen follows Sievert's law (linear dependence of H2 flow rate on the square root of the pressure difference), but as the hydrogen concentration in the binary mixture decreases, the flux is not linear, showing a downward convexity towards the pressure axis. Due to the use of partial pressure, the effect of dilution has been included, and the fact that CH4 can be considered inert, mass transfer limitation from the bulk to the membrane surface (concentration polarization) is the most likely explanation for this phenomenon; it becomes more important in the case of high flux, high selectivity membranes. Similar behavior was observed in Pd 0.8Ag 0.2; 2.5 μm thick supported films.
[0185] The hydrogen flow rate of different H2-CH4 mixtures with hydrogen concentrations ranging from 10% to 70% is shown ( Fig. 20 ) and purity ( Fig.21 ). A 20 cm Pd-Ag ceramic supported membrane was used for the above tests. The trend was also compared with the pure gas test. The retentate pressure was varied from 8 bar to 40 bar, while the permeate pressure was maintained at 0.15 bar with a vacuum pump. Due to concentration polarization, the hydrogen permeability is significantly reduced, especially when working at low hydrogen content. The purity is also significantly reduced compared to the purity obtained with pure H2. The reason may be that due to the high permeability of hydrogen, the concentration of pollutants close to the membrane surface is higher.
[0186] exist Fig. 22 In the graph, the hydrogen permeance of binary mixtures of H2 / N2, H2 / CO2 and H2 / CH4 as a function of the H2 content in the mixture at 400°C and 3 bar total pressure (vacuum on the permeate side) is shown for PdAg supported membranes (see Melendez J. et al. 2017). It is clearly noticed that when the hydrogen percentage in the feed decreases, then the hydrogen permeance also decreases. In addition, the permeated hydrogen flux decreases very linearly from 100% to 0% H2 and is very similar for different H2 mixtures.
[0187] Example 7. Correlation between partial pressure difference and hydrogen flux in water-saturated Al-CMSM
[0188] The hydrogen flow rate as a function of the hydrogen partial pressure difference was tested at 20°C for various H2 / CH4 and H2 / N2 mixtures and Al-CMSM carbonized at 550°C (CMSM-550) after exposure to ambient humidity. It can be seen that the correlation between the hydrogen partial pressure difference and the hydrogen flux is almost linear and is independent of the H2 concentration in the mixture and the gas tested ( Fig.23 ), which proves that concentration polarization does not affect the H2 flow through the membrane.
[0189] Results and Advantages of the Water-Saturated Al-CMSM of the Invention
[0190] The effect of water adsorption on the membrane was also tested in Al-CMSM carbonized at 600°C. The effect of water vapor treatment on the permeated gas purity was investigated by first removing water under N2, heating at 150°C, and performing permeation tests with dry and humidified gases. H2 / CH4 mixtures containing 10% H2 were tested at different temperatures (20°C, 50°C, 70°C and 100°C) at different H2 partial pressures, and the relative increase in purity obtained under humidified conditions was evaluated. Significant performance improvements were shown after humidification of the membrane, especially at elevated temperatures.
[0191] H2 / CH4, H2 / N2, H2 / CO2, CO2 / CH4 and CO2 / N2 gas mixtures are expected to have similar effects since the adsorption of water in the walls of the pores promotes the penetration of more absorbent and smaller molecules.
[0192] Therefore, the water-saturated Al-CMSM showed competitive and promising performance compared with commercial membranes for gas separation in mixtures, especially at high pressures - since there are no mass transfer limitations. Moreover, when operating under humidified conditions, gas purity was further improved due to water adsorption, especially at high temperatures.
[0193] From Comparative Examples 1 and 2 and the above examples, it can be seen that the water-saturated Al-CMSM of the present invention is advantageous for the following reasons:
[0194] - Water-saturated Al-CMSM provides significantly higher purity compared to dry Al-CMSM, especially at higher temperatures.
[0195] The H2 permeation on the -Pd membrane is carried out between 300 and 500 °C, while in the Al-CMSM it can be carried out at room temperature, so considering similar permeation, the Al-CMSM has lower operating costs.
[0196] -Pd based membranes are very expensive, whereas Al-CMSM is produced from very cheap phenolic resin.
[0197] -The flux on the Pd membrane depends on ΔP 0.5, while the flux on Al-CMSM depends on ΔP. Therefore, the H2 flux on Al-CMSM is higher at high pressure and low temperature.
[0198] - In mixed gas permeation, for Pd membranes, the hydrogen flux decreases with decreasing H2 concentration; for Al-CMSM, the flux is almost constant (rather than concentration polarization).
[0199] Example 8
[0200] Carbon membrane for water vapor permeation
[0201] In water permeation, depending on the water pressure and temperature, condensation may occur, resulting in the presence of a monolayer of adsorbed water and free water (gas) ( Fig.24 ). By increasing the pressure and decreasing the temperature, the water in the pores increases.
[0202] Effect of carbonization temperature on water penetration
[0203] As mentioned above, the hydrophilicity of the carbon membrane can be changed by varying the carbonization temperature. For the Al-CMSM of Example 2.2, the water permeability at different temperatures and a pressure difference of 3 bar was measured and Fig.25 . Independent of the carbonization temperature, the lowest permeability was obtained when the experiment was carried out at 150 °C; as explained before, this is due to the condensation of water in the pores. For membranes carbonized at 500 and 550 °C, the highest permeability was obtained at a permeation temperature of 200 °C; for membranes carbonized at 600 and 650 °C, the maximum value shifted to 250 °C ( Fig.25 ). When the carbonization temperature of the membrane increases to 750 and 850 °C, the permeation peak shifts again to 200 °C.
[0204] The permeation peak is related to the hydrophilicity of the pores. Without wishing to be bound by theory, although as the carbonization temperature increases from 550°C to 600°C, the number and size of the pores increase, exposing more hydrophilic groups; the number of activated carbons also increases, which react with water to form new hydrophilic groups. Increasing the temperature from 650°C, the hydrophilic groups are removed and condensation reactions occur between the activated carbons, which reduces the porosity of the membrane and, therefore, the water permeation. This is more pronounced for the membrane carbonized at 850°C; therefore, the water permeability at this temperature is lower than that at 750°C. The presence of more hydrophilic groups in the pores binds the water more firmly to the pores, which requires more energy (higher temperature) to remove.
[0205] Water / air ideal permselectivity
[0206] For the Al-CMSM of Example 2.2, the permeabilities of various gases (N2, H2, CH4, CO, CO2) at different temperatures were measured, and their water / gas ideal selectivities (i.e., water permeation selectivities) were calculated. Fig.26 For the gases tested, all membranes showed selectivity for water, since it has the smallest kinetic diameter (0.26 nm, molecular sieve transport) and has a greater affinity for the pores (adsorption-diffusion transport).
[0207] The water permeation selectivity depends on the carbonization temperature and the permeation temperature.
[0208] Regardless of the carbonization temperature, the highest selectivity is obtained when the permeation is carried out at about 200°C, except for the H2O / N2 mixture, where the maximum is obtained at about 250°C for the membrane carbonized at 750°C. Probably, at about this carbonization temperature, the number and size of the pores are most favorable for the permeation of water; below this temperature, there are fewer pores, while above this temperature, water begins to condense in the pores, thereby reducing the porosity, hydrophilicity and pore size. In fact, the lowest selectivity is obtained for the membrane carbonized at 1000°C.
[0209] In general, for the gases tested, the highest selectivity was obtained for the membranes carbonized at 750 °C.
[0210] Fig.26 The function relationship between the kinetic diameter and the permeation temperature of the Al-CMSM of Example 2.2 carbonized at different temperatures for water / gas ideal selectivity is shown. For all carbonization temperatures, the highest selectivity is obtained for water / N2. The selectivity of water for CO2 and H2 is lower than that of N2, probably due to the larger kinetic diameter of the latter. CO is larger than N2 and has a lower selectivity. CO is a polar compound, which can adsorb on the hydrophilic pores of the carbon membrane, increasing the adsorption-diffusion mechanism of permeation. Comparing CO and CH4, CH4 is larger than CO, so its permeability is lower. Regarding N2 and CH4, CH4 is a symmetrical molecule that is not easily polarized, on the other hand, N2 has poor symmetry and may be more easily polarized, which increases the dipole-induced dipole interaction with the polar pores.
[0211] The lowest selectivity was observed with H2 because the size of the molecule is slightly larger than water; in addition, water can form hydrogen bonds with the pores, which increases the adsorption-diffusion permeation.
[0212] References
[0213] 1.Llosa MA et al."Composite-alumina-carbon molecular sieve membranesprepared from novolac resin and boehmite.Part I:Preparation,characterizationand gas permeation studies",Int.J.Hydrogen Energy.2015,vol.40,pp.5653–5663.
[0214] 2.M.A.Llosa et al."Composite-alumina-carbon molecular sieve membranesprepared from novolac resin and boehmite.Part II:Effect of the carbonizationtemperature on the gas permeation properties",Int.J.Hydrogen Energy.2015,Vol.40,pp.3485–3496
[0215] 2.Campo MC et al."Carbon molecular sieve membranes from cellophanepaper"Journal of Membrane Science,2010,vol.350,pp.180-188;
[0216] 3.Teixeira M et al."Composite phenolic resin-based carbon molecularsieve membranes for gas separation",Carbon 2011,vol.49,pp.4348-4358;
[0217] 4.Teixeira M et al."Carbon–Al2O3–Ag composite molecular sievemembranes for gas separation"Chem.Eng.Res Des.2012,vol.90,pp.2338-2345.
[0218] 5. Rodrigues SC, et al. "Preparation and characterization of carbonmolecular sieve membranes based on resorcinoleformaldehyde resin" J.Memb.Sci.2014, vol.459, pp.207-216.
[0219] 6.Nguyen C.,Do,DD"Adsorption of supercritical gases in porousmedia:determination of micropore size distribution".J.Phys.Chem.B.1999,103(33),6900-8,and
[0220] 7.Nguyen C et al. "The structural characterization of carbon molecularsieve membrane (CMSM) via gas adsorption" J.Memb.Sci., 2003, 220(1-2)177-82.
[0221] 8.Melendez J et al., "Preparation and characterization of ceramicsupported ultra-thin(~1μm)Pd-Ag membranes", J.Memb.Sci.2017, vol.528, pp.12–23.
[0222] For reasons of completeness, various aspects of the invention are listed in the following numbered clauses:
[0223] 1. A water-saturated carbon molecular sieve membrane, which can be obtained by the following method:
[0224] a) providing a hydrophilic carbon molecular sieve membrane (CMSM) comprising pores with a pore size of 0.25 nm to 0.55 nm for molecular sieving, and pores with a pore size of greater than 0.55 nm to 0.90 nm for adsorption diffusion and a negligible amount of pores greater than 0.90 nm, so that a curve of N2 permeability versus permeation pressure at room temperature and a pressure of 1 to 4 bar has a zero slope or a negative slope; and
[0225] b) humidifying the membrane until a water-saturated carbon molecular sieve membrane is obtained.
[0226] 2. The water-saturated carbon molecular sieve membrane according to clause 1, wherein the CMSM is a composite alumina-carbon molecular sieve membrane (Al-CMSM).
[0227] 3. A water-saturated carbon molecular sieve membrane according to clause 2, wherein the Al-CMSM has a nitrogen content of 0.1 wt% to 4.0 wt%, an alumina content of 2.5 wt% to 50% and a carbon content of 50 wt% to 95 wt% relative to the total weight of the membrane.
[0228] 4. A method for separating a gas from a gas mixture, the method comprising:
[0229] a) providing a water-saturated membrane as defined in any one of clauses 1 to 3;
[0230] b) providing a gas mixture comprising at least two gases;
[0231] c) feeding said gas mixture into said water-saturated CMSM at a temperature of 5° C. to 300° C. so as to obtain a retentate and a permeate, wherein the feeding is carried out at such a pressure that the partial pressure of said gas in the retentate is higher than the partial pressure of said gas in the permeate and that the membrane is a water-saturated membrane.
[0232] 5. The method according to clause 4, wherein the temperature of step (c) is 5°C to 250°C, 5°C to 120°C, 15°C to 120°C, 15°C to 100°C, 15°C to 70°C or 20°C to 50°C.
[0233] 6. A method according to clause 4 or 5, wherein the at least two gases have a polarizability of 2 to 27 and at least one of the at least two gases has a kinetic diameter of less than 0.55 nm, and wherein if the at least two gases have a kinetic diameter of less than 0.55 nm, the difference in the kinetic diameter between the at least two gases is equal to or greater than 0.01 nm and / or the difference in the polarizability between the at least two gases is equal to or greater than 1 nm 3 .
[0234] 7. A method according to clause 6, wherein the at least two gases are selected from He, H2O, Ne, H2, NO, Ar, NH3, N2, O2, CO, CO2, CH4, C2H4, C2H6, propylene, propane, H2S, methanol and ethanol.
[0235] 8. A method according to any one of clauses 4 to 7, wherein the gas mixture comprising at least two gases is selected from H2 / CH4; H2 / N2; H2 / CO2; CO2 / CH4; CO2 / N2; O2 / N2; and biogas.
[0236] 9. The method according to clause 8, wherein the gas mixture comprises 5% to 20% H2 and 95% to 80% CH4, and wherein step c) is carried out at a hydrogen partial pressure difference equal to or higher than 3 bar and at a temperature of 40°C or below.
[0237] 10. The method according to clause 8, wherein the at least two gases are CO2 and N2 and the gas mixture comprises 10% to 20% CO2 and 65% to 75% N2, in particular about 15% CO2 and about 70% N2.
[0238] 11. The method according to clause 8, wherein the at least two gases are H2 and CO2, and the gas mixture comprises 55% to 65% H2 and 30% to 40% CO2, in particular about 60% H2 and about 35% CO2.
[0239] 12. The method according to clause 8, wherein the gas mixture comprising at least two gases is biogas and CO2 is removed from the biogas.
[0240] 13. Use of a water-saturated CMSM as defined in clauses 1 to 3 for separating a gas from a gas mixture.
[0241] 14. Use of a water-saturated CMSM as defined in clauses 1 to 3 for solvent dehydration.
[0242] 15. Use of a water-saturated CMSM as defined in clauses 1 to 3 as a membrane reactor.
Claims
1. A water-saturated carbon molecular sieve membrane, obtained by: i) providing a hydrophilic carbon molecular sieve membrane, i.e., a CMSM, comprising, as defined herein, pores having a pore size of 0.25 nm to 0.55 nm for molecular sieving, pores having a pore size of greater than 0.55 nm to 0.90 nm for adsorptive diffusion, and a negligible amount of pores greater than 0.90 nm, such that a plot of N2 permeance versus permeate pressure at room temperature and pressures of 1 to 4 bar, as defined herein, has a zero slope or a negative slope; and ii) humidifying the CMSM obtained in step i) to obtain a water-saturated CMSM by: - treating it with water vapor for a certain period of time at a temperature ranging from 5°C to 180°C and at atmospheric pressure and a relative humidity above 95% so that after further treatment with water vapor, the permeation flux of non-adsorbable gases at 4 bar at the temperature at which the CMSM has been treated with water vapor is constant during a specific period of time.
2. A water-saturated carbon molecular sieve membrane obtained by: i) providing a hydrophilic carbon molecular sieve membrane, i.e., a CMSM, comprising, as defined herein, pores having a pore size of 0.25 nm to 0.55 nm for molecular sieving, pores having a pore size of greater than 0.55 nm to 0.90 nm for adsorptive diffusion, and a negligible amount of pores greater than 0.90 nm, such that a plot of N2 permeance versus permeate pressure at room temperature and pressures of 1 to 4 bar, as defined herein, has a zero slope or a negative slope; and ii) humidifying the CMSM obtained in step i) to obtain a water-saturated CMSM by: - Exposing it to a water-saturated N2 or He gas stream by bubbling the gas into a tank filled with water at a temperature between 5°C and 180°C, so that after further exposure to the water-saturated N2 or He gas stream, the permeate flux of the non-adsorbable gas is constant during a specific period of time at 4 bar and the above temperature. 3 . The water-saturated carbon molecular sieve membrane according to claim 1 , wherein the CMSM is a composite alumina-carbon molecular sieve membrane, i.e., Al-CMSM.
4. The water-saturated carbon molecular sieve membrane according to claim 3, wherein the Al-CMSM has a nitrogen content of 0.1 wt% to 4.0 wt%, an alumina content of 2.5 wt% to 50 wt% and a carbon content of 50 wt% to 95 wt% relative to the total weight of the Al-CMSM.
5. A method for preparing a water-saturated composite alumina-carbon molecular sieve membrane, i.e., Al-CMSM, comprising: i) Preparation of hydrophilic Al-CMSM by: -Providing a porous α-Al2O3 carrier; - preparing a solution containing 5-20 wt% of phenolic resin, 0.5-5 wt% of formaldehyde, 0.1-2 wt% of ethylenediamine, and 0.1-5 wt% of boehmite in N-methyl-2-pyrrolidone, and heating the solution to perform a prepolymerization process to obtain a coating solution; - impregnating the porous α-Al2O3 support with a coating solution to obtain a coated support; - drying the coated support at a temperature of 70 to 120° C. in order to complete the polymerization process; - carbonizing the dried coated support at a carbonization temperature of 450° C. to 750° C. in order to obtain Al-CMSM; ii) humidifying the Al-CMSM prepared in step i) to obtain water-saturated Al-CMSM by: - treating it with water vapor for a certain period of time at a temperature ranging from 5°C to 180°C and at atmospheric pressure and a relative humidity above 95% so that after further treatment with water vapor, the permeation flux of non-adsorbable gases at 4 bar at the temperature at which the CMSM has been treated with water vapor is constant during the specific period of time.
6. A method for preparing a water-saturated composite alumina-carbon molecular sieve membrane, i.e., Al-CMSM, comprising: i) Preparation of hydrophilic Al-CMSM by: -Providing a porous α-Al2O3 carrier; - preparing a solution containing 5-20 wt% of phenolic resin, 0.5-5 wt% of formaldehyde, 0.1-2 wt% of ethylenediamine, and 0.1-5 wt% of boehmite in N-methyl-2-pyrrolidone, and heating the solution to perform a prepolymerization process to obtain a coating solution; - impregnating the porous α-Al2O3 support with a coating solution to obtain a coated support; - drying the coated support at a temperature of 70 to 120° C. in order to complete the polymerization process; - carbonizing the dried coated support at a carbonization temperature of 450° C. to 750° C. in order to obtain Al-CMSM; ii) humidifying the Al-CMSM prepared in step i) to obtain water-saturated Al-CMSM by: - Exposing it to a water-saturated N2 or He gas stream by bubbling N2 or He gas into a tank filled with water at a temperature between 5°C and 180°C, so that after further exposure to the water-saturated N2 or He gas stream, the permeation flux of the non-adsorbable gas is constant during a specific period of time at 4 bar and the above temperature.
7. The method according to claim 5 or 6, wherein the phenolic resin is a novolac resin.
8. The method according to claim 5 or 6, wherein the carbonization temperature is 450°C to 700°C.
9. A water-saturated Al-CMSM obtainable by the method of claim 5 or 6.
10. A method for separating a gas from a gas mixture, the method comprising: a) providing a water-saturated carbon molecular sieve membrane as defined in any one of claims 1 to 4 or a water-saturated Al-CMSM as defined in claim 9; b) providing a gas mixture comprising at least two gases; and c) feeding said gas mixture into said water-saturated CMSM at a temperature comprised between 5°C and 300°C so as to obtain a retentate and a permeate, wherein the feeding is carried out at such a pressure that the partial pressure of the gases in the retentate is higher than the partial pressure of the gases in the permeate and that a difference in permeation is observed compared to the same CMSM without the humidification step so as to obtain a water-saturated membrane at the feed temperature and pressure.
11. The method according to claim 10, wherein the at least two gases have a polarizability of 2 to 27 and at least one of the at least two gases has a kinetic diameter of less than 0.55 nm, and wherein if the at least two gases have a kinetic diameter of less than 0.55 nm, the difference in the kinetic diameter between the at least two gases is equal to or greater than 0.01 nm and / or the difference in the polarizability between the at least two gases is equal to or greater than 1 nm 3 .
12. The method of claim 11, wherein the at least two gases are selected from He, H2O, Ne, H2, NO, Ar, NH3, N2, O2, CO, CO2, CH4, C2H4, C2H6, propylene, propane, H2S, methanol and ethanol.
13. The method according to claim 10, wherein the gas mixture containing at least two gases is selected from H2 / CH4; H2 / N2; H2 / CO2; CO2 / CH4; CO2 / N2; O2 / N2; and biogas, which is a gas mixture mainly containing methane and carbon dioxide and small amounts of other gases.
14. The method according to claim 13, wherein the other gas is H2, H2S, N2 or water vapor.
15. The method according to claim 13, wherein the gas mixture comprises 5% to 20% H2 and 95% to 80% CH4, and wherein step c) is carried out at a hydrogen partial pressure difference equal to or higher than 3 bar and at a temperature of 40°C or below.
16. The method of claim 13, wherein the at least two gases are CO2 and N2, and the gas mixture comprises 10% to 20% CO2 and 65% to 75% N2.
17. The method of claim 13, wherein the at least two gases are H2 and CO2, and the gas mixture comprises 55% to 65% H2 and 30% to 40% CO2.
18. The method of claim 13, wherein the gas mixture comprising at least two gases is biogas, and CO2 is removed from the biogas, wherein biogas is a gas mixture comprising methane and carbon dioxide.
19. Use of a water-saturated carbon molecular sieve membrane as defined in any one of claims 1 to 4 or a water-saturated Al-CMSM as defined in claim 9 for solvent dehydration.
20. Use of a water-saturated carbon molecular sieve membrane as defined in any one of claims 1 to 4 or a water-saturated Al-CMSM as defined in claim 9 as a membrane reactor.
Citation Information
Patent Citations
Carbon membrane and method of manufacturing the same
US20100083837A1
